A CRITICAL REVIEW ON NUTRACEUTICALS IN MADHUMEHA (DIABETES) - Srinivasulu, Bandari; Prasad, Goli Penchala; Narayana, Ala (International Journal of Ayurveda and Pharma Research, 2015)
Diabetes mellitus is a well-known clinical syndrome since antiquity. Ayurveda mainly focuses on the role of diet in Prameha and Madhumeha, which is akin to Diabetes. Nutraceuticals are food or food products that provide health and medical benefits, including the prevention and treatment of disease. Traditional Indian diets are functional and used both as food and medicine. Although in recent scientific studies these diets are evaluated for rich source of dietary fiber (whole grains and vegetables), antioxidants and other active principles suitable for diabetes. Primarily, they have been selected and used based on fundamental principles of Ayurveda, such as their Rasa, Guna, Virya, Vipaka, Prabhava, and so on. Reviewing the characteristic properties along with important antidiabetic properties of conventional system of medicine, accentuates the role of these diets in Diabetes. The correlation further emphasizes the way to include or to evaluate more Nutraceuticals for the benefit of Diabetic population. Diabetes is a complex disease with multiple variations. Nutraceuticals too have variant properties and belong to various dietetic groups, such as Kodrava (grain variety: Paspolum scrobiculatum Linn.), Adhaki (red gram: Cajamus indicus Spreng.), Yava (Barley: Hordeum vulgare Linn.), Mudga (green gram: Phaseolus radiatus Linn.), Kuluttha (horse gram: Dolichos biflorus Linn.), Amalaki (Indian goose berry: Emblica officinalis Gaertn.), Meti (fenugreek: Trigonella foenum-graecum Linn.), Karavellaka (bitter gourd: Momordica charantia Linn.), Jambu (java plum: Syzygium cumini (Linn.) Skeels.), Navapatola (young: Tricosanthes dioica Roxb.), Matsyakshi (Alternanthera sessiles Linn.) R. Br. etc.